First-in-human study to assess the pharmacokinetics, tolerability, and safety of single-dose oxybutynin hydrochloride administered via a microprocessor-controlled intravaginal ring. (31st December 2023) - de Laat, Willem; Pagan, Lisa; Malcolm, R. Karl; Wiegerinck, Maarten; Nickolson, Victor; Huisman, Bertine; Stuurman, Rik; van Esdonk, Michiel; Klarenbeek, Naomi
Abstract: Polymeric drug-releasing vaginal rings are useful for both local and systemic administration of drugs via the intravaginal route. Typically, they provide continuous sustained or controlled release of drug(s) over extended time periods, thereby avoiding overdose and improving adherence. This first-in-human study (EudraCT number: 2020-0050044-30) evaluated the pharmacokinetics, safety, and tolerability of a single dose of oxybutynin administered by a novel microprocessor-controlled vaginal ring (MedRing). Eight healthy female subjects received an electronically controlled single intravaginal dose of 3 mg oxybutynin hydrochloride (100 mg/mL) dissolved in 1:1 water/propylene glycol administered via MedRing. Following dosing, MedRing was kept in situ for up to 6 h. Blood samples were collected 1 h prior to oxybutynin dosing and subsequently at regular intervals post-dose for the assessment of plasma concentrations of oxybutynin and its active metabolite N -desethyloxybutynin. The results showed that MedRing efficiently administered oxybutynin via the intravaginal route, resulting in plasma oxybutynin levels comparable to orally administered oxybutynin. The mean ± standard deviation pharmacokinetic parameters for oxybutynin were C max 5.4 ± 2.7 ng/mL, AUCinf 34.9 ± 17.4 h ng/mL, t 1/2 8.5 ± 3.5 h and for N-desethyloxybutynin were C max 3.9 ± 2.5 ng/mL, AUCinf 51.1 ± 43.1 h ng/mL, t 1/2 7.7 ± 5.9 h. No serious adverse events were reported. The study demonstrates that intravaginal administration of oxybutynin hydrochloride using the MedRing device was well tolerated.